The Development of Learning activity using KWL Plus to promote Thai reading and writing abilities for Vietnamese students - VU, THANH HANG; Khechornphak, Thanyaluck (Journal for Developing the Social and Community, 2026)
Background and Aims: Growing economic, educational, and cultural cooperation between Thailand and Vietnam has increased the demand for Thai language proficiency among Vietnamese learners. However, the substantial differences between the Thai and Vietnamese writing systems make learning Thai reading and writing particularly challenging for beginners. Conventional teacher-centered online instruction provides limited opportunities for activating prior knowledge and promoting active learning. Therefore, the KWL Plus strategy, which encourages learners to connect prior knowledge with new learning and organize information systematically, was employed to improve students’ Thai literacy. This study aimed to: (1) develop Thai reading and writing proficiency among Vietnamese students through KWL Plus learning activities based on the 70% criterion, and (2) examine their learning achievement after participating in the activities. Methodology: Classroom action research was conducted with six beginner-level Vietnamese students over three action cycles (24 instructional hours). Research instruments included 12 KWL Plus lesson plans, Thai reading and writing achievement tests, behavioral observation forms, teaching reflection diaries, and student interview forms. Quantitative data were analyzed using percentage, mean, and standard deviation, while qualitative data were analyzed through content analysis. Results: The 12 lesson plans were evaluated by experts and received a high suitability rating (mean = 4.42). Students’ performance improved across the three action cycles, with mean scores of 83.81%, 89.53%, and 87.86%, respectively. Overall learning achievement reached 89.17%, exceeding the predetermined 70% criterion. These findings indicate that the KWL Plus strategy effectively enhanced Thai reading and writing proficiency and can serve as an effective instructional approach for beginner-level foreign language learners.